Flow-induced transverse vibration of a circular cylinder close to a plane wall at small gap ratios. (October 2020) - Chen, L.F.; Wu, G.X.
Abstract: Numerical simulations of flow-induced transverse vibration of a near-wall cylinder with small gap to diameter ratios ( e / D  ≤ 0.5) at R e = 200 are performed based on the Navier-Stokes equations using a finite volume method based OpenFOAM codes. Multi-block mesh is used. As the cylinder is very close the wall, remeshing is regularly applied during the body oscillation to avoid over distortion of the grid. A model to account for the collision of the cylinder with the wall is adopted, in which when the gap between the cylinder and the wall is smaller than a critical value, the direction of its velocity is reversed. Simulations are made for low mass ratio, relevant to the cases in hydrodynamics. The results show that the motion amplitude generally increases with the reduced velocity U * = U / ( f n D ) first and then decreases after reaching a peak, and there is no obvious hysteretic transition. When e / D decreases, the largest amplitude decreases, and the reduced velocity at which the largest amplitude occurs increases. The results also indicate that the wall has a significant effect on the natural frequency of the cylinder, suggesting that the fluid force has components strongly affected by the body acceleration and displacement. When e / D decreases, the frequency at which the largest amplitude occurs becomes larger than the natural frequency obtained from the ratio of the cylinder stiffness to the summation of mass and the added mass. It is observed that, in all the cases when e / D  ≤ 0.5, the anti-clockwise vortices in the wake of the cylinder are suppressed and only one single vortex of 1S type is shed downstream. As e / D decreases, the clockwise vortex shed from the upper part of the cylinder remains strong, and the anti-clockwise vortex from the lower part of the cylinder gradually becomes weaker, and the vortex street is less deflected upwards.